WHAT ARE THE PRACTICALITIES OF MAPPING MINOR CURRICULUM? - Fatima, Sadia; Evans, Phillip (Journal of Ayub Medical College Abbottabad, 2015)
Background: Many under graduate medical colleges are in the process of mapping their curriculum. This process was investigated in three typical medical schools of Pakistan by semi-structured interviews of the senior faculty members. Conclusions were made and discussed. Methods: Semi-structured interviews were conducted with the senior faculty curriculum managers concerned with mapping Human Nutrition in three medical schools in Khyber Pakhtunkhwa (KPK) province of Pakistan. Issues relating to the principles and processes used in mapping minor curriculum themes were explored, and the costs and benefits were identified. Results: It was reported that fixed curricular criteria were published by the Pakistan Medical and Dental Council (PMDC) and therefore curriculum mapping was not necessary, with an intention to map minor curriculum themes eventually. Learning outcomes of curriculum themes were not recognized or described. There is no consensus by curriculum managers, evaluating authorities, implementing authorities or senior faculty members about the principles and process of curriculum mapping. Public pressure may cause resistance to any change in the curricula. Action was limited by lack of resources. Conclusion: Lack of awareness of the significance of curriculum mapping, as a tool for quality assurance, evaluation and management is prevalent and is the main factor in limiting this technique. Further research is required to establish what has been done in other medical colleges of Pakistan regarding mapping of curriculum themes and what the difficulties are. This analysis will lead to a strategy for improvement, and collaboration of all medical colleges in Pakistan.